Multiple cyclic nucleotide-gated channels coordinate calcium oscillations and polar growth of root hairs - Brost, Christa; Studtrucker, Tanja; Reimann, Ronny; Denninger, Philipp; Czekalla, Jennifer; Krebs, Melanie; Fabry, Ben; Schumacher, Karin; Großmann, Guido; Dietrich, Petra (The plant journal, 2019)
Calcium gradients underlie polarization in eukaryotic cells. In plants, a tip-focused Ca2+-gradient is fundamental for rapid and unidirectional cell expansion during epidermal root hair development. Here we report that three members of the cyclic nucleotide-gated channel family are required to maintain cytosolic Ca2+ oscillations and the normal growth of root hairs. CNGC6, CNGC9 and CNGC14 were expressed in root hairs, with CNGC9 displaying the highest root hair specificity. In individual channel mutants, morphological defects including root hair swelling and branching, as well as bursting, were observed. The developmental phenotypes were amplified in the three cngc double mutant combinations. Finally, cngc6/9/14 triple mutants only developed bulging trichoblasts and could not form normal root hair protrusions because they burst after the transition to the rapid growth phase. Prior to developmental defects, single and double mutants showed increasingly disturbed patterns of Ca2+ oscillations. We conclude that CNGC6, CNGC9 and CNGC14 fulfill partially but not fully redundant functions in generating and maintaining tip-focused Ca2+ oscillations, which are fundamental for proper root hair growth and polarity. Furthermore, the results suggest that these calmodulin-binding and Ca2+-permeable channels organize a robust tip-focused oscillatory calcium gradient, which is not essential for root hair initiation but is required to control the integrity of the root hair after the transition to the rapid growth phase. Our findings also show that root hairs possess a large ability to compensate calcium-signaling defects, and add new players to the regulatory network, which coordinates cell wall properties and cell expansion during polar root hair growth.